Insights into ionic medicine: cerium reduces the presence of reactive oxygen species and favors osteogenic over adipogenic differentiation in human mesenchymal stromal cells - Westhauser, Fabian; Jacobsen, Valentin; Zheng, K.; Merle, Christian; Boccaccini, A. R.; Renkawitz, Tobias; Kunisch, Elke (Journal of trace elements in medicine and biology, 2025)
The guided application of metallic ions in bone tissue engineering (BTE) has recently gained popularity being described as one important example of ionic medicine (IM). BTE aims to enhance osteogenic differentiation of precursor cells like bone-marrow-derived mesenchymal stromal cells (BMSCs) and, by that, regenerate bone tissue. BMSCs however can also differentiate into adipogenic lineage. It is known that elevated levels of reactive oxygen species (ROS) stimulate BMSC towards (undesired) adipogenic differentiation. One ion, that is particularly interesting for application in IM-guided BTE is cerium (Ce) since it acts as a self-regenerating ROS-scavenger and has already been successfully incorporated in biomaterials. Ce has demonstrated pro-osteogenic, anti-adipogenic and anti-oxidative effects before, however, so far, there is no direct comparative study available that analyzes these effects on human BMSCs in one and the same setting. Therefore, in this study, the influence of Ce nitrate (CeN) on the expression of osteogenic, adipogenic and ROS-scavenging genes in BMSCs was evaluated as well as its impact on formation of an osseous extracellular matrix (ECM), lipid formation and physical ROS presence. The presence of CeN improved BMSCs viability, enhanced proliferation, and reduced ROS-levels. Furthermore, CeN suppressed adipogenesis while osteogenic differentiation and the formation and maturation of the ECM were enhanced. The presence of CeN reduced the physical presence of ROS and the gene expression patterns shifted towards an anti-oxidant profile. Ce therefore constitutes an attractive ion for application in IM-guided BTE. Further research is necessary to clarify the biological mechanisms and pathways that are involved in the Ce-mediated modulation of BMSC differentiation.
Gesehen am 28.10.2025